2009
DOI: 10.1016/j.jmmm.2009.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling between Gd and Pr ions and magnetocaloric effect in Gd0.5Pr0.5Al2 compound

Abstract: a b s t r a c tIn this work, we report the theoretical and experimental investigations on the magnetic and magnetocaloric properties for Gd 0.5 Pr 0.5 Al 2 compound in different magnetic fields. The magnetization features indicate that Gd 0.5 Pr 0.5 Al 2 is ferrimagnetic at low temperatures. We also present data from X-ray magnetic circular dichroism (XMCD) experiments for this compound, with which we have confirmed that the magnetic moments of the Pr ions are antiparallel to the magnetic moments of the Gd ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…The measured value of the Curie temperature for GdAl 2 (x = 0) is approximately in agreement with literature values reported in Refs. [27][28][29]. It is clearly seen that Ce substitution slightly decreases the Curie temperatures of the samples.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…The measured value of the Curie temperature for GdAl 2 (x = 0) is approximately in agreement with literature values reported in Refs. [27][28][29]. It is clearly seen that Ce substitution slightly decreases the Curie temperatures of the samples.…”
Section: Methodsmentioning
confidence: 87%
“…In RE 1-x RE' x Al 2 (where RE and RE' = rare earth elements) type alloys, the nature of the magnetic ordering and the Curie temperature are strongly dependent on the intersublattice exchange interactions, and therefore on the spin-orbit couplings [32] between rare-earth elements. In many previous studies it has been reported that in systems in which either both rare-earth elements are light (from Ce to Sm) or both are heavy (from Gd to Yb), the resulting exchange coupling is ferromagnetic, whereas for lightheavy combinations the exchange coupling is ferrimagnetic [15,29,35]. Recent experimental and theoretical works have confirmed the existence of ferrimagnetic coupling in Gd 1-x Pr x Al 2 alloys [15,29].…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations